Immunological Approaches and Different Strategies for Vaccine Development Against SARS-COV-2 - Babakir-Mina, Muhammed (Kurdistan Journal of Applied Research, 2020)
Globally, SARS-CoV-2 outbreak is considered as pandemic viral infection by the World Health Organization (WHO). In the immunological response aspect, a very limited understanding has been progressed, mainly innate and adaptive immunity responses toward the virus. SARS-COV-2 causes severe respiratory disease and sometimes ended with the death. The body of the patients has ability to develop the immunity to cure the patient and more importantly both humoral and cellular immunity have studied against SARS-COV-2. There are different immune responses against the viral infection as it has seen in other previous diseases such as SARS-COV and MESR. On the base on immune response detected in recovered patients, scientists have started to develop the vaccines. Moreover, there are different strategies that used by researchers and pharmacological companies to develop vaccines including attenuated or killed viruses, RNA of a spike protein, and vector expressing a particular protein of the virus. The common antibodies have detected to work against SARS-COV-2 in sera of infected or recovered patients are immunoglobin G ( IgG) and immunoglobin M (IgM). The sera of patients recovered from COVID-19, after tittering of immunoglobulins (IgG titer) can be used for either treatment of disease or prophylaxis of infection by SARS-COV-2. This study gives an update on the current immunological approaches and vaccination strategies for the emerging SARS-COV-2, and discusses the challenges and hurdles to overcome for developing efficacious vaccines against this dangerous pathogen.